2006
DOI: 10.1111/j.1742-4658.2006.05163.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol linked to enhanced angiogenesis in rat model of choroidal neovascularization

Abstract: Age-related macular degeneration (AMD) is the leading cause of blindness in the Western world in people aged over 55. Exudative (i.e. wet-type) AMD is characterized by the development of new vessels within the choroid of the eye (i.e. choroidal neovascularization; CNV) [1]. This neovasculature penetrates Bruch's membrane and grows beneath the retinal pigment epithelium and neurosensory retina [2][3][4][5][6][7]. Many different growth factors have been implicated in the development of choroidal angiogenesis [8]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Choroidal angiogenesis (CNV) causing the wet-type AMD is the leading cause of irreversible visual loss in individuals over age 55 (1)(2)(3)(4)(5)(6)(7)(8)(9). We have recently shown that the formation of MAC, as a result of complement activation via the alternative pathway, is essential for the development of laser-induced CNV in mice (6,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choroidal angiogenesis (CNV) causing the wet-type AMD is the leading cause of irreversible visual loss in individuals over age 55 (1)(2)(3)(4)(5)(6)(7)(8)(9). We have recently shown that the formation of MAC, as a result of complement activation via the alternative pathway, is essential for the development of laser-induced CNV in mice (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…Although the nonexudative (dry) form of AMD is more prevalent, catastrophic vision loss is more frequently associated with the exudative (wet) form, specifically from the complication of neovascularization of the choroid (1)(2)(3)(4)(5)(6)(7)(8)(9). Several risk factors have been implicated in the pathogenesis of new choroidal vessel formation (choroidal neovascularization; CNV) in exudative AMD (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Evidence from both human and animal studies supports a key role for complement activation in the development of CNV (7)(8)(9)(10)(11). We demonstrated that membrane attack complex (MAC) formation via the alternative pathway activation is important for the release of angiogenic growth factors that are critical for the induction of CNV in mouse model (9).…”
mentioning
confidence: 92%
“…Induction of CNV, Administration of rCD59-APT542 and rsCD59a-Fc-CNV was induced by laser photocoagulation in C57BL/6 mice with an argon laser (50-m spot size, 0.05 s duration, 260 milliwatt) as previously described by us (7)(8)(9). Three laser spots were placed in each eye close to the optic nerve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation